Examining the Attitudes and Experiences of Nurses Working in a High Security Forensic Psychiatry Unit from a Psychiatric Perspective - Örüm, Dilek; Atmaca, Murad (My University, 2025)
Aim: This study aims to examine the approaches, attitudes, and experiences of nurses working in a High Security Forensic Psychiatry Unit (HSFPU) towards psychiatric disorders, conditions, and treatments and to reveal the associated factors. Material and Method: This cross-sectional study was conducted with nurses working at Elazığ Fethi Sekin City Hospital HSFPU who agreed to participate in the study. The participants filled out the Nurses’ Attitudes Towards Forensic Psychiatric Patients Scale (NAFPPS) along with a questionnaire including various variables. Results: Thirty-two nurses (22 females (68.80%), 10 males (31.20%)) were included in the study. Twenty-two nurses (31.20%) did not have sufficient knowledge of the Penal Code of Türkiye 32 (PCT 32). The psychiatric disorder that nurses found easiest to predict was bipolar spectrum disorder (43.80%), while the one that nurses found most difficult to predict was schizophrenia spectrum disorder (62.50%). The illicit substance that caused the most difficulty in nursing care was methamphetamine for 19 nurses (59.40%). Nurses' command of psychiatric terminology was not at the desired level. Twenty-three nurses (71.90%) thought that antidepressants caused addiction. Almost all of the nurses (96.90%) thought that antisocial and borderline personality traits make nursing care difficult. According to regression analysis, working duration in HFSPU predicts NAFPPS willingness to provide care subscale (constant p<0.001; working duration in HFSPU p=0.039), while NAFPPS willingness to provide care subscale predicts routine learning of psychiatric diagnosis in nursing care (constant p=0.048, NAFPPS willingness to provide care p=0.037). Conclusion: This study demonstrated that nurses' knowledge and experience levels regarding psychiatric treatment practices were quite high, but not at the desired level regarding forensic and psychiatric terminology. It was suggested that the necessary improvements would be provided through in-service training including psychiatric nursing, forensic psychiatric nursing, psychiatry, psychology, and social services.
Keywords: Psychiatric nursing; Nurse; nursing care; forensic psychiatry; forensic nursing